Languages in Membrane Computing: Some Details for Spiking Neural P Systems - Gheorghe Paun (Springer, 2006)
After a brief introduction to membrane computing, pointing out the more important intersections with formal language theory, we survey a series of recent results related to spiking neural P systems used as devices for handling languages. Several open problems are formulated.